FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PEMBERIAN VITAMIN A PADA IBU NIFAS DI WILAYAH KERJA PUSKESMAS TEBING TAHUN 2018 - Wahyuni, Tri; Mona, Silvia (Universitas Batam, 2018)
The puerperium stage begins when the baby is born or the placenta is released and ends when gestational organs has returned to their pre-pregnancy state. The puerperal period is important because it deals with a critical period of time for both the mother and the newborn baby. The purpose of this study is to determine factors correlated to treatment of Vitamin A for postpartum mothers. This study used an analytical research design with cross sectional approach done at the Tebing Health Center started from May to June 2018. The population was 44 postpartum mothers selected using purposive sampling technique. The result indicates 31 respondents (70.5%) with poor knowledge on Vitamin A treatment for the postpartum mothers, menwhile, 31 respondents (70.5%) have low educational background. On the other hand, 26 respondents (59.1%) are not completed their Vitamin A treatment. Conversely, Chi Square test ensues an impact of knowledge levels of the mothers with p = 0.000 <0.05, and motherâ€™s education with p = 0.001 <0.05, to their puerperal visits to the Puskesmas Tebing with p = 0.000 < 0.05. Therefore, it can be concluded that there is correlation between these crucial factors and the vitamin A treatment in postpartum mothers. For the suggestions, it is hoped that respondents of this study to be able to apply and implement the information and knowledge gained in real life situations.Â